GRACE Follow‐On Laser Ranging Interferometer Measurements Uniquely Distinguish Short‐Wavelength Gravitational Perturbations. Issue 16 (13th August 2020) - Ghobadi‐Far, Khosro; Han, Shin‐Chan; McCullough, Christopher M.; Wiese, David N.; Yuan, Dah‐Ning; Landerer, Felix W.; Sauber, Jeanne; Watkins, Michael M.
Abstract: We examined the first‐ever laser ranging interferometer (LRI) measurements of inter‐satellite tracking acquired by Gravity Recovery and Climate Experiment (GRACE) Follow‐On satellites. Through direct along‐orbit analysis of instantaneous inter‐satellite measurements, we demonstrate the higher sensitivity of LRI (than K‐band microwave ranging [KBR]) to anomalies associated with the Earth static gravity field at high spatial resolutions of 100–200 km. We found that LRI captures gravitational signals as small as 0.1 nm/s 2 at 490 km altitude, improved by 1 order of magnitude from KBR. This allows LRI to uniquely detect un‐/mis‐modeled short‐wavelength gravitational perturbations. We employed all LRI data in 2019 to validate various state‐of‐the‐art global static gravity field models and show that LRI measurements, even over 1 month, can distinguish subtle differences among the models computed from ~15 years of GRACE KBR and ~4 years of Gravity Field and Steady‐State Ocean Circulation Explorer (GOCE) gradiometry data. Ultra‐precise LRI measurements will be yet another critical data set for future gravity field model development. Key Points: We examined the first‐ever measurements of inter‐satellite laser ranging interferometer (LRI) from GRACE Follow‐On satellites LRI measures static gravity perturbations as small as 100 km by more than 1 order of magnitude better than microwave‐based measurements Laser data are accurate enough to detect subtle errors in global gravity field models from ~15 years of GRACE and ~4 years of GOCE data